2004
DOI: 10.1074/jbc.m402855200
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for the Catalytic Activity of Human Serine/Threonine Protein Phosphatase-5

Abstract: Serine/threonine protein phosphatase-5 (PP5) affects many signaling networks that regulate cell growth and cellular responses to stress. Here we report the crystal structure of the PP5 catalytic domain (PP5c) at a resolution of 1.6 Å. From this structure we propose a mechanism for PP5-mediated hydrolysis of phosphoprotein substrates, which requires the precise positioning of two metal ions within a conserved Asp 1 is a water molecule). The structure of PP5c provides a structural basis for explaining the except… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
155
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 103 publications
(161 citation statements)
references
References 68 publications
6
155
0
Order By: Relevance
“…A new water molecule fills the cavity left by one of the missing oxygen atoms of the phosphate. The conformations of almost all PP5 residues coordinating Cdc37-S13E, the active site water molecules, and the Mn 2+ ions are unchanged compared with the phosphate-bound holo structure (17). The exception is Arg275, for which the guanadinium group has flipped.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…A new water molecule fills the cavity left by one of the missing oxygen atoms of the phosphate. The conformations of almost all PP5 residues coordinating Cdc37-S13E, the active site water molecules, and the Mn 2+ ions are unchanged compared with the phosphate-bound holo structure (17). The exception is Arg275, for which the guanadinium group has flipped.…”
Section: Resultsmentioning
confidence: 81%
“…The exception is Arg275, for which the guanadinium group has flipped. The conformation of the Cdc37 peptide is, therefore, that of a trapped substrate, because all residues and active site waters are in orientations that are suitable for the inline nucleophilic attack proposed for the catalytic mechanism (17).…”
Section: Resultsmentioning
confidence: 99%
“…Subsequent studies revealed that cantharidin functions as an inhibitor of several PPP family serine/threonine protein phosphatases (PPases), acting as a weak inhibitor of calcineurin (PP2B) and a potent inhibitor of three families (PP1, PP2A, and PP5) of structurally related PPases (14 -16). Recent structural studies revealed that the cantharidin-sensitive PPases share a common catalytic mechanism (17), and structure/activity relationship studies indicate that cantharidin (15) and fostriecin (18), another natural product with antitumor activity, both act to inhibit the catalytic activity of the same PPP family phosphatases (15,17,18). Human genetic studies have identified four highly homologous isoforms of PP1 (PP1a, PP1h/y, PP1g1, and PP1g2), two nearly identical isoforms of PP2A (PP2a and PP2Ah), and two PPases (designated PP4 and PP6) that, at the level of their primary amino acid sequence, share f54% and 60% identity with PP2Aa, respectively (for review, see ref.…”
Section: Introductionmentioning
confidence: 99%
“…PP5 is an okadaic acid/cantharidin/microcystin-sensitive member of the PPP family of Ser/Thr phosphatases, which also includes PP1, PP2A, PP4, and PP6 (7)(8)(9). Currently the roles played by PP5 in biology and disease are not clear.…”
mentioning
confidence: 99%